(untitled) (Journal of Economics and Sustainability, 2024)
Based on county-level panel data from 2014 to 2017 in Jing-Jin-Ji region, employing SDEM model to analyze the impact and heterogeneity of digital inclusive finance on poverty alleviation. The results show that, first, digital inclusive finance exerts significant poverty alleviation effect, and this effect focuses on local region, having no apparent spillover effects on neighborhood counties. Second, the poverty alleviation effects of digital inclusive finance are heterogeneous, the effects of index of Coverage and Usage, and basic, upgraded and supported digital finance service are different in Jing-Jin-Ji, Hebei and Poverty Area Samples. Third, digital inclusive finance exerts bigger poverty alleviation effect on the less developed region and poverty region, showing the effect of Corner Overtaking.